John Floyd papers - Floyd, John, 1783-1837.
Correspondence relating to Floyd's nomination for vice president on the Jackson ticket (1831) and to the presidential election of 1832. Correspondents include Duff Green, Littleton Waller Tazewell, and John Tyler.
In part, handwritten transcripts.
Surgeon and U.S. representative from and governor of Virginia.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Green, Duff, -- 1791-1875 -- Correspondence; Jackson, Andrew, -- 1767-1845.; Tazewell, Littleton Waller, -- 1774-1860 -- Correspondence; Tyler, John, -- 1790-1862 -- Correspondence; Elections -- United States -- 1832.; Virginia -- Politics and government -- 1775-1865.